Coverham Abbey - one of North Yorkshire's ancient gems - Lloyd, Chris (Darlington and Stockton Times, 2018)
Keywords: coverham

Archaeological Investigations at Coverham Abbey, North Yorkshire 1995–2015 - Pinnock, Dave (Yorkshire Archaeological Journal, 2016)
Coverham Abbey near Middleham, North Yorkshire is the site of a former Premonstratensian monastery. As well as a fine late medieval gatehouse, there are some standing remains of the abbey church including parts of the eastern elevation of the chancel, the north transept, the western elevation of the nave, the south transept, and three standing pillars of the arcade of the nave’s south aisle. Later dwellings on the site incorporate substantial masonry from the abbey’s west claustral range. A number of small scale, developer-funded archaeological investigations have been undertaken since 1995 that shed light on the layout and design of the medieval monastery. In particular, the various investigations have revealed the layout of the hitherto unknown east and south claustral ranges, as well as further aspects of the west range. The buried remains of an elaborately carved lavatorium arcade were also found, which is a highly significant example of monastic decorative architecture.
Keywords: coverham

A 14th-Century Sculpted Arcade from Coverham Abbey - Harrison, Stuart A. (Journal of the British Archaeological Association, 2013)
Keywords: coverham